The Rule of Law Crisis and Political Economy. The Case of Poland (Economic and Political Thought, 2024)
In recent years, the phenomenon of the rule of law crisis has been widely discussed. This issue was raised especially by researchers representing legal and political sciences. However, the rule of law also has an important socioeconomic dimension. The socioeconomic context of the rule of law can be considered on the one hand in the context of institutional economics, and on the other hand in the realm of political economy. In the empirical part, in relation to the crisis of the rule of law, an approach based on the achievements of comparative political economy was used, which made it possible to examine how the crisis of the rule of law has contributed to the perpetuation of the current model of a “dependent market economy” based on foreign direct investments carried out mainly outside the most innovative sectors.
Keywords: rule of law crisis, authoritarian capitalism, political economy, dependent market economy, Poland